2019
DOI: 10.5009/gnl18189
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Diagnostic Yield of the Standard 22-Gauge Needle and the New 20-Gauge Forward-Bevel Core Biopsy Needle for Endoscopic Ultrasound-Guided Tissue Acquisition from Pancreatic Lesions

Abstract: Background/Aims To compare the diagnostic yield of 20-gauge forward-bevel core biopsy needle (CBN) and 22-gauge needle for endoscopic ultrasound (EUS)-guided fine needle aspiration (FNA) of solid pancreatic masses. Methods The use of 20-gauge CBN was prospectively evaluated for 50 patients who underwent EUS-FNA from June 2016 to December 2016. Data were compared with those obtained by a retrospective study of 50 consecutive patients who underwent EUS-FNA using standard … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
22
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 22 publications
(29 reference statements)
0
22
0
Order By: Relevance
“…To overcome these disadvantages of EUS-FNA, several novel needles have been introduced for EUS-guided fine needle biopsy (EUS-FNB). [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] Recently, a three-plane symmetric needle with Franseen geometry has been developed for performing EUS-FNB. [15][16][17][18][19][20] While rapid on-site evaluation (ROSE) reportedly increases the diagnostic performance and decreases the number of passes, 21 its role in EUS-FNB is not fully established in clinical practice.…”
Section: Introductionmentioning
confidence: 99%
“…To overcome these disadvantages of EUS-FNA, several novel needles have been introduced for EUS-guided fine needle biopsy (EUS-FNB). [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] Recently, a three-plane symmetric needle with Franseen geometry has been developed for performing EUS-FNB. [15][16][17][18][19][20] While rapid on-site evaluation (ROSE) reportedly increases the diagnostic performance and decreases the number of passes, 21 its role in EUS-FNB is not fully established in clinical practice.…”
Section: Introductionmentioning
confidence: 99%
“…The frequency of AEs observed following EUS-guided tissue acquisition for solid pancreatic lesions was approximately 0 % to 2 % [14,17,20]. However, there are few reports of AEs for small solid pancreatic lesions.…”
Section: Discussionmentioning
confidence: 99%
“…Histological diagnosis is also important to distinguish pancreatic cancer from neuroendocrine neoplasms. Several studies have reported that EUS-FNB is more useful in diagnostic yield than EUS-FNA 13 14 15 16 17 18 19 . However, there are only a few reports on use of EUS-FNB in small solid pancreatic lesions.…”
Section: Discussionmentioning
confidence: 99%
“…EUS-FNA demonstrates a fairly high diagnostic ability (nearly 95% sensitivity and specificity) for solid malignant pancreatic lesions [42,43]. The use of thick core biopsy needles [44] and high-negative-pressure aspiration methods [45] has increased the acquisition rate for obtaining core tissue samples. This, in turn, has enabled the determination of the probable nature of the whole pancreatic mass and even the classification of intermediate inflammatory and neoplastic conditions, such as IMTs.…”
Section: Discussionmentioning
confidence: 99%